2018
DOI: 10.1186/s13058-018-1003-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune characterization of breast cancer metastases: prognostic implications

Abstract: BackgroundTumor-infiltrating lymphocytes (TILs) evaluated in primary breast cancer (BC) convey prognostic information. Limited data in the metastatic setting are available.MethodsSecondary lesions from 94 BC patients, 43 triple-negative (TN) and 51 HER2-positive, were evaluated for TILs and expression of CD8, FOXP3, and PD-L1 by immunohistochemistry.ResultsTILs levels on metastasis were generally low (median 5%) and did not differ between TN and HER2+ tumors. Younger patients showed significantly lower TILs (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 32 publications
7
63
0
Order By: Relevance
“…In contrast to NSCLC, where regulatory approval for anti‐PD1/PD‐L1 therapy (pembrolizumab) is based on PD‐L1 positivity assessed on tumor cells , in BC, PD‐L1 seems to be predominantly expressed by stromal compartment . However, so far, no consistent data exist on the possible biological and clinical implications of a differential expression of PD‐L1 by either tumor cells or tumor‐infiltrating immune cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to NSCLC, where regulatory approval for anti‐PD1/PD‐L1 therapy (pembrolizumab) is based on PD‐L1 positivity assessed on tumor cells , in BC, PD‐L1 seems to be predominantly expressed by stromal compartment . However, so far, no consistent data exist on the possible biological and clinical implications of a differential expression of PD‐L1 by either tumor cells or tumor‐infiltrating immune cells.…”
Section: Methodsmentioning
confidence: 99%
“…The immune landscape of metastatic lesions may be even more complex when considering that a trend in the opposite direction with regard to TILs has been reported. In particular, results from two large retrospective cohorts of patients with MBC showed that TILs tended to decrease from primary to metastatic lesions in the TN subtype , especially in patients receiving CT (for the advanced disease) prior to metastasis biopsy .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-micrometer-thick sections were cut from FFPE blocks and mounted onto slides. The slides were processed and stained as previously reported [26].…”
Section: Tma and Immunohistochemistrymentioning
confidence: 99%
“…BRCA1 is a suppressor gene, whose dysfunction is linked to a higher risk of developing cancer, such as inhibition of DNA repair enzymes Poly [ADP-Ribose] Polymerase 1 (PARP1) [24]. Moreover, our team has shown in TNBC tumors that the association between nuclear PARP1 and cytoplasmic NHERF1 (Na+/H+ Exchanger Regulatory Factor 1) expression, a scaffolding protein with oncogenic activity [25], identified a subgroup of patients with a shorter survival [26].…”
Section: Introductionmentioning
confidence: 98%